2003
DOI: 10.1175/1520-0426(2003)20<987:iavori>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Validation of Range Imaging on a UHF Radar Wind Profiler

Abstract: The available range resolution of pulsed radar wind profilers is usually limited by bandwidth restrictions. Range imaging (RIM) has recently been developed as a means of mitigating these limitations by operating the wind profilers over a small set of distinct transmitter frequencies. A constrained optimization method can then be used to generate high-resolution maps of the reflectivity field as a function of range. This paper presents a description of how the RIM technique has been recently implemented on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 26 publications
(9 reference statements)
1
18
0
Order By: Relevance
“…As discussed already, the Turbulent Eddy Profiler (TEP) developed at the University of Massachusetts Microwave Remote Sensing Laboratory (MIRSL) provides three-dimensional fine-scale imagery of the intensity of clear-air backscatter and motion of the air with 30 m resolution between 200 m and 2.0 km altitude (Mead et al, 1998), and other high resolution developments have been presented or are currently underway (e.g., Yu and Brown, 2004;Lehmacher et al, 2007;Rüster et al, 1998;Cho et al, 1996b;Hassenpflug et al, 2008;Kilburn et al, 1995;Woodman et al, 2007;Chilson et al, 2003). Cho et al (1996b) in fact achieved 20 m resolution, although they used a non-MST radar to do that.…”
Section: Imaging Sdi and Fdimentioning
confidence: 99%
“…As discussed already, the Turbulent Eddy Profiler (TEP) developed at the University of Massachusetts Microwave Remote Sensing Laboratory (MIRSL) provides three-dimensional fine-scale imagery of the intensity of clear-air backscatter and motion of the air with 30 m resolution between 200 m and 2.0 km altitude (Mead et al, 1998), and other high resolution developments have been presented or are currently underway (e.g., Yu and Brown, 2004;Lehmacher et al, 2007;Rüster et al, 1998;Cho et al, 1996b;Hassenpflug et al, 2008;Kilburn et al, 1995;Woodman et al, 2007;Chilson et al, 2003). Cho et al (1996b) in fact achieved 20 m resolution, although they used a non-MST radar to do that.…”
Section: Imaging Sdi and Fdimentioning
confidence: 99%
“…5. Time-range plot of (top) brightness produced by the Fourier-based method, (center) brightness produced by the Capon method, and (bottom) backscattered power expressed in decibels (Chilson et al, 2003). The data was collected with the Platville 915-MHz tropospheric wind profiler.…”
Section: Advantage Of Range Resolution Enhancement Using Multiple Frementioning
confidence: 95%
“…RIM also contributes to efficient usage of frequencies. Chilson et al (2003) pointed out that for the RIM measurement shown in Fig. 5, the spurious intensity of frequency power spectrum of transmitted pulses was smaller than the 0.4-μs transmitted pulse width which also uses 2.5-MHz bandwidth (see their Fig.…”
Section: Advantage Of Range Resolution Enhancement Using Multiple Frementioning
confidence: 99%
“…In its early stage of development, the frequency-hopped technique used only two frequencies, alternately, for transmission and was used to examine a Gaussian-distributed atmospheric layer structure in the range gate. Chilson et al (2003) implemented the frequency-hopped technique using more than two frequencies in an ultra-high-frequency (UHF) radar, which facilitates the investigation of Kelvin-Helmholtz instabilities and the dynamics of subsidence inversion. The frequency-hopped technique with several frequencies, commonly referred to as range imaging (RIM; Palmer et al, 1999) or frequency domain radar interferometric imaging (FII; Luce et al, 2001), has been useful for remote sensing of the atmosphere.…”
Section: Introductionmentioning
confidence: 99%